High-Dose Intravenous Immunoglobulin as a Therapeutic Option for Deteriorating Patients With Coronavirus Disease 2019 - Cao, Wei; Liu, Xiaosheng; Bai, Tao; Fan, Hongwei; Hong, Ke; Song, Hui; Han, Yang; Lin, Ling; Ruan, Lianguo; Li, Taisheng (Open forum infectious diseases, 2020)
Abstract The outbreak of coronavirus disease 2019 (COVID-19) has spread rapidly in China. Until now, no definite effective treatment has been identified. We reported on 3 patients with severe COVID-19 who received high-dose intravenous immunoglobulin (IVIg) with satisfactory recovery. Based on these observations, randomized studies of high-dose IVIg should be considered in deteriorating patients infected with COVID-19.